Eksistensi Pendidikan Pondok Pesantren Untuk Masyarakat Labuhanbatu - Harahap, Aziddin; Rahayu, Sri; Harahap, Hasmi Syahputra (ALACRITY : Journal of Education, 2024)
The purpose of this community service focuses on the Existence of Islamic Boarding School Education for the Labuhanbatu Community, where this is carried out at the Darul Husna Langpayung Modern Islamic Boarding School, South Labuhanbatu Regency so that twelfth grade students, especially those who will leave Islamic boarding schools, can understand the role and existence of Islamic boarding schools, especially in Labuhanbatu. south. The sample in this activity was all students and teachers at the Darul Husna Langpayung Islamic Boarding School. The method in this service is a qualitative descriptive approach. Where the analysis developed by describing how the existence of Islamic boarding schools in South Labuhanbatu and can provide insight, discourse and evidence for the development of Islamic boarding schools, especially in South Labuhanbatu. Based on the activities that have been carried out, it is hoped that the existence of Islamic boarding schools will continue to grow. Because a strong foundation in religion is needed for the progress of the nation, especially the South Labuhanbatu area. The shared hope is that Islamic boarding schools must continue to exist in the midst of technological progress in today's society.